Long-term preservation of digital archival documents in trustworthy digital repositories - Chaves, Elisa Maria Lopes [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2023)
The process of preserving digital records must consider consolidated tools that consider the life cycle of the record, in addition to parameters that consider storage and long-term preservation. For archival documents, there are national and international norms and standards that advocate the use of Reliable Digital Archival Repositories. The object of this work introduces the premises of a trusted repository and its requirements and highlights the main repositories available in the area. Through an exploratory and qualitative research, three repositories will be analyzed, they are: Archivematica, Repository of Authentic Digital Objects and DSpace that are presented and evaluated regarding the requirements of a Reliable Digital Archival Repository. In the comparative research presented, it is observed that Archivematica and the Repository of Authentic Digital Objects are considered Reliable Digital Archival Repositories and DSpace is more used as a storage repository. Archivematica stands out for being the most used, in addition to the more extensive bibliography. It is concluded that in addition to the use of a Reliable Digital Archival Repository, it must be understood within a well-designed and widespread Digital Preservation Policy and combined with an access tool that is also compatible with archival standards and norms.
Keywords: Archivematica; Reliable Digital Archival Repositories; Digital preservation